Selective binding of benzoquinone with a Pt-II-cyclophane constructed on the skeleton of N,N `-bis(salicylidene)-p-phenylenediamine: synthesis and spectroscopic studies - Kumari, Niraj; Prajapati, Rishikesh; Dixit, Mudit; Mishra, Lallan (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2009)
The Schiff base NN'-bis(salicylidene)-p-phenylenediamine has been complexed with Pt(en)Cl-2 and the resulting Pt-II-cyclophane, [Pt(en)L](2)center dot 4PF(6), reacted with phenol, resorcinol, hydroquinone or benzoquinone in DMSO solution. Their binding has been monitored by the variation in the corresponding UV-visible and emission spectral patterns. The binding properties are compared with the earlier reported Zn-II-cyclophane [Zn(bpy)L](2) (bpy = 2,2'-bipyridine). A few solid adducts of phenol and benzoquinone with the Pt-II-cyclophane complex and hydroquinone as well as that of resorcinol with the Zn-cyclophane have also been synthesized and characterized.
Keywords: Coordination chemistry; Cyclophanes; Metallocyclophanes; platinum; Schiff bases

Scandium-decorated MOF-5 as potential candidates for room-temperature hydrogen storage: a solution for the clustering problem in MOFs - Dixit, Mudit; Maark, Tuhina Adit; Ghatak, Kamalika; Ahuja, Rajiv; Pal, Sourav (Journal of Physical Chemistry C, 2012)
Transition-metal-based systems show promising binding energy for hydrogen storage but suffer from clustering problem. The effect of light transition metal (M = Sc, Ti) decoration, boron substitution on the hydrogen storage properties of MOF-5, and clustering problem of metals has been investigated using ab initio density, functional theory. Our results of solid-tate calculations reveal that whereas Ti clusters strongly Sc atoms do not suffer from this problem when decorating MOF-5. Boron substitution on metal-decorated MOF-5 enhances the interaction energy of both the metals with MOF-5. Sc-decorated MOF-5 shows a hydrogen storage capacity of 5.81 wt % with calculated binding energies of 20-40 kJ/mol, which ensures the room-teniperature applicability of this hydrogen storage material.